Website Promosi Pariwisata: Solusi Digital untuk Eksplorasi Potensi Desa - Santoso, Hadi; Lukman Hakim (JPM: Jurnal Pengabdian Masyarakat, 2025)
Ciputri Village, located in Pacet Subdistrict, Cianjur Regency, possesses promising natural tourism potential. However, this potential has not been optimally promoted due to the lack of adequate digital infrastructure, particularly in leveraging web-based platforms for tourism information dissemination. One of the key issues is the limited utilization of information technology, especially the absence of a village website integrated with location-based features. Additionally, the lack of technical skills among village officials and local residents in managing and maintaining web systems has hindered efforts to develop digital tourism strategies. In response to these challenges, a community service program initiated by LLDIKTI Region 3 and carried out by a team from Universitas Mercubuana, Universitas Pertamina, and Akademi Maritim Djadajat conducted a series of socialization and training activities. These activities aimed to introduce, train, and enhance the digital capabilities of village officials and residents through location-based website development and management. The program included a Focus Group Discussion (FGD) to identify local needs, hands-on technical workshops, and feedback sessions to assess participants’ understanding. This initiative is expected to build digital competence in Ciputri Village and serve as a foundation for transforming it into a smart tourism village empowered by information technology.